Regulation of the Compatibility of Tax-Liability Aggravating Factors with the Requirements of the Protection of Human Rights and Fundamental Freedoms - Gruodis, Povilas (Teisė, 2019)
This article represents the results of an analysis focused on the protection of human rights and fundamental freedoms and tax norms provided in Article No. 140, Part. 4 of the Law on Tax Administration of the Republic of Lithuania, where a list of tax-liability aggravating factors is provided. The results of the analysis are provided in the conclusions, together with recommendations on how to improve the present regulation.